Effects of microstructure on the dynamic properties of TA15 titanium alloy. (October 2019) - Arab, Ali; Chen, Pengwan; Guo, Yansong
Highlights: Four different microstructures of TA15 titanium alloy are obtained using different heat treatment conditions. High strain rate response of the different microstructure of the TA15 was investigated. TA15 with martensitic α structure shows the highest strength in most of the strain rate. TA15 with coarse lamellar structure shows the lowest hardness, this microstructure has the lowest strain rate sensitivity compared to other samples. Abstract: To improve the understanding regarding the effect of microstructure on the dynamic behaviour of titanium alloy, four different microstructures of TA15 titanium alloy are obtained using different heat treatment conditions. Then, the hardness and dynamic behaviour of these samples are investigated. Dynamic load testing of samples are performed by the split Hopkinson pressure bar (SHPB) at different strain rates (500–2600 s −1 ). The material behaviour during the tests are measured and recorded. The relation between the microstructure and mechanical properties is studied. Results indicate that the water quenched sample with martensitic α structure possesses the highest hardness. The bimodal microstructure reveals good plastic deformation and appropriate strength. Water quenched sample reveals the high strain rate sensitivity between the strain rate of 500 s −1 and 900 s −1 ; however, after this point the strain rate sensitivity of sample is decreasing. Sample with bimodal structure (no heat treatment) shows the highest increase in temperature during the dynamic loading in all strain rates. Furthermore, the microstructural observation of the samples show that the formation of the adiabatic shear band is highly influenced by the microstructure type. In the water quenched samples the adiabatic shear band is formed in lowest strain rate compare to the other samples. These results suggest that the TA15 microstructure considerably influences the dynamic properties. Graphical abstract: Image, graphical abstract